Multiple Intelligences Learning and Equity in Middle School Mathematics Education - Young, Brian Edward (Curtin University, 2003)
This study offers a new approach to raising mathematics achievement through the synthesis of Multiple Intelligences theory and Self-Efficacy theory. It proposes that the opportunity to learn through intellectual strengths will raise mathematics achievement both directly from students' increased understanding and indirectly through raising students' self-efficacy for mathematics. A mathematics learning program was developed for year eight students in a rural secondary school based on tasks resonating with their intellectual strengths. Both quantitative and qualitative indicators were used to compare the effects of the Multiple Intelligences learning program with the standard delivery of the mathematics curriculum to year eight students over their first term of study. After nine weeks participation in the Multiple Intelligences learning program, students demonstrated improved engagement and more positive attitudes in mathematics classes relative to their peers receiving standard instruction. The expected gains in mathematics achievement and self-efficacy were not demonstrated within the one-term span of the study. Assessment of the fidelity of implementation of the principles of Multiple Intelligences theory was confirmed through assessment of the classroom learning environment. Analysis of the reasons for the lack of differentiation revealed limitations in the traditional measures used for assessing the mathematics learning outcomes gained within the Multiple Intelligences program.The loss of available year eight classroom instruction time from institutional assessment requirements and school policy decisions were found to be higher for the class receiving the Multiple Intelligences program than for the comparison class, and this is a significant confounding variable. It is concluded that significant changes to school organisational structures and assessment procedures are required before the cognitive and affective advantages of Multiple Intelligences learning may be realised optimally in the mathematics classroom.